1995
DOI: 10.1007/bf03349741
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spironolactone on testosterone fractions and sex-hormone binding globulin binding capacity in hirsute women

Abstract: This study explored the effect of the anti-androgen spironolactone on sex-hormone binding globulin (SHBG) and the distribution of circulating testosterone (T) into various free and bound fractions in seven women with hirsutism assessed before and then monthly for three months on a regimen of spironolactone, 100 mg bid as the sole therapeutic agent. Blood samples were taken at each assessment time for a battery of androgen parameters and serum T fractions studies. None of the women were judged obese based upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…92 In healthy men 93 and in men with prostatic carcinoma, 94 it decreased concentrations of DHEA as well as testosterone and androstenedione. Other studies have not shown changes in DHEA and/or DHEA-S concentrations, potentially because of small sample size, 95,96 or the previous administration of dexamethasone to decrease steroid concentrations. 97…”
Section: Spironolactonementioning
confidence: 98%
“…92 In healthy men 93 and in men with prostatic carcinoma, 94 it decreased concentrations of DHEA as well as testosterone and androstenedione. Other studies have not shown changes in DHEA and/or DHEA-S concentrations, potentially because of small sample size, 95,96 or the previous administration of dexamethasone to decrease steroid concentrations. 97…”
Section: Spironolactonementioning
confidence: 98%